EFFECT OF PHYSICAL AND MECHANICAL PROPERTIES OF SA 333 GRADE 9 STEEL ON SMAW METHOD WELDING WITH E 7018 ELECTRODES - T. Jukdin Saktisahdan; Zufri Hasrudy Siregar; Mawardi Mawardi; Abdul Latif S (Universitas Muhammadiyah Semarang, 2023)
Welding is a permanent connection method; one method is MAW (Shielded Metal Arc Welding). This is welding using an electric flame in an arc to melt metal with heat. This use can be used in almost all positions and is considered relatively economical with quality depending on the user. In this study, the aims were to determine the tensile strength of SA333 grade 9 carbon steel and to test the hardness value of the base metal in the HAZ area and the weld metal. From the analysis of this study, a tensile test was carried out after welding the material, as well as a hardness test which was visualized by the macro and micro structures of the test material. This study concludes that the results of tensile testing on SA333 grade 9 carbon steel Raw Material have a maximum value of 6450 and a fracture stress of 4900 MPa, as well as the hardness value on the base metal, the HAZ area, and the weld metal area has the highest hardness value of 4530 HVN compared to of base metal and HAZ.